2020
DOI: 10.1155/2020/1314586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Informatization Performance of Construction Industrialization EPC Enterprises in China

Abstract: An enormous amount of investment has been spent towards informatization for the construction industrialization engineering, procurement, and construction (EPC) enterprises in China; however, the performance output remains uncertain. This paper aims to evaluate the informatization performance of the construction industrialization enterprises in China based on a proposed evaluation framework. The proposed framework entails a hierarchical input and output structure; the input metrics include 4 first-level and 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…In fact, the policy requiring the implementation of prefabricated buildings has greatly promoted the development of China's prefabricated industry [108]. Although the Chinese government has proposed a series of policies for the development of prefabrication in recent years [109], the implementation of prefabrication in China still lags behind those in other developed countries [110]. Previous studies have shown concerns about potentially high capital costs or even high total costs in prefabricated construction projects [111].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the policy requiring the implementation of prefabricated buildings has greatly promoted the development of China's prefabricated industry [108]. Although the Chinese government has proposed a series of policies for the development of prefabrication in recent years [109], the implementation of prefabrication in China still lags behind those in other developed countries [110]. Previous studies have shown concerns about potentially high capital costs or even high total costs in prefabricated construction projects [111].…”
Section: Discussionmentioning
confidence: 99%
“…e ratio of z ij in the index j in the evaluation matrix is calculated as (4), and the contribution degree of all indicators of the evaluation matrix to the attribute is calculated as (5).…”
Section: Entropymentioning
confidence: 99%
“…erefore, the EPC model has gradually become the most common construction project delivery method for engineering projects in recent years [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, prefabricated buildings have been widely adopted in China due to their preferable characteristics in the construction stage compared to the traditional cast-inplace construction [1][2][3][4], which is mainly assembled on-site using prefabricated components that are connected using the vertical sleeve method [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%